Docetaxel chemotherapy plus androgen-deprivation therapy in high-volume disease metastatic hormone-sensitive prostate cancer in Chinese patients: an efficacy and safety analysis - Zhuifeng Guo; Xuwei Lu; Fan Yang; Liang Qin; Ning Yang; Jiawen Wu; Hang Wang (European Journal of Medical Research, 2022)
Abstract Objective To investigate the efficacy and safety of docetaxel chemotherapy combined with androgen-deprivation therapy for patients with high-volume disease metastatic hormone-sensitive prostate cancer. Methods 153 cases of high-volume disease metastatic hormone-sensitive prostate cancer in Minhang Hospital between January 2018 and December 2019 were analyzed retrospectively, including the number of patients, age, initial PSA level, Gleason score, TNM stage and ECOG score. 90 patients in the endocrine therapy group received continuous ADT, and 63 patients in the combined chemotherapy group received docetaxel plus ADT. The progression-free survival time (time from initiation of prostate cancer treatment to progression to CRPC), PSA response rate, and adverse reactions were compared between the two groups. Results All 153 cases were closely followed up for a period of 12.3–35.3 months, with a median follow-up time of 23.5 months. The median time to reach the lowest point of PSA in the two groups was 6.3 months and 7.9 months (P = 0.018) in the combination chemotherapy group and the ADT group alone, with 27 (42.9%) and 12 (13.3%) cases in the two groups Within 12 months of treatment, PSA decreased to below 0.2 ng/ml (P = 0.02), and progression-free survival was 16.9 months (6.5–28.5 months) and 11.2 months (4.3–22.7 months) in the two groups. (P < 0.001). There were 18 cases (28.6%) and 54 cases (60%) in the two groups with disease progression (P < 0.001). There were 6 cases (9.5%) and 15 cases (16.7%) in the combination chemotherapy group and the ADT group died of prostate cancer and related complications, respectively. All 63 cases in the combined chemotherapy group completed 6 cycles of chemotherapy. 39 (61.9%) cases experienced varying degrees of neutropenia, of which 12 (19%) experienced grade 3–4 neutropenia, with 6 cases (9.5%) developed febrile neutropenia. 30 cases (47.6%) had toxic reactions in the digestive system, and 3 case (4.3%) had grade 3 liver dysfunction. 27 cases (42.8%) had skin and mucosal toxicity. 9 cases (14.3%) had mild fluid retention. No blood and digestive toxicity were observed in the ADT group. 33 cases (52.4%) and 48 (53.3%) of the two groups had symptoms of afternoon hot flashes and fatigue, (P = 0.961). Conclusion Docetaxel chemotherapy combined with endocrine therapy could be one of effective treatments for delaying castration resistance of HVD-mHSPC, which could prolong PFS effectively and obtain a higher PSA response rate, high safety under close monitoring, and controllable adverse reactions.